Development of Interactive Educational Songs to Enhance Students' Motivation in Reading and Writing - Wibowo, Hamid Sakti; Sidqi, Kholfan Zubair Taqo; Sandi, Muhammad Aris; Ningrum, Aqnassari Mutsla (IQRA`: Jurnal Perpustakaan dan Informasi, 2025)
This study explores the development of interactive educational songs using digital technology and a Design Thinking approach to enhance reading and writing motivation among students at Wahid Hasyim University (Unwahas). Low literacy motivation remains a critical issue in higher education, prompting the need for innovative solutions. Music, as an engaging medium, was utilized to create interactive songs tailored to student preferences. The Design Thinking process ensured user-centered development, beginning with empathy to understand student challenges, followed by prototyping and testing for constructive feedback. The songs feature relevant educational themes, memorable melodies, and meaningful lyrics. Expert evaluations rated the media and content quality at 96% and 90%, respectively, indicating "very good" results. Large group trials with 25 students demonstrated a 41.7% increase in literacy motivation, with improved engagement and interest in reading and writing activities. This research highlights the potential of digital tools in fostering innovative learning methods and contributes to advancing educational practices at Unwahas.